Free fatty acid receptors - Milligan, Graeme ; Kimura, Ikuo (Springer, 2020)
Ligands at free fatty acid receptor 1 (GPR40) / Takafumi Hara -- Ligands at the free fatty acid receptors 2/3 (GPR43/GPR41) / Graeme Milligan, Daniele Bolognini, Eugenia Sergeev -- Pharmacological tool compounds for the free fatty acid receptor 4 (FFA4/GPR120) / Steffen V.F. Hansen, Trond Ulven -- Application of GPCR structures for modelling of free fatty acid receptors / Irina G. Tikhonova -- Using biosensors to study free fatty acid receptor pharmacology and function / Brian D. Hudson -- Key questions for translation of FFA receptors: from pharmacology to medicines / Arthur T. Suckow, Celia P. Briscoe -- Polymorphic variation in FFA receptors: functions and consequences / Atsuhiko Ichimura -- The role and future of FFA1 as a therapeutic target / Julien Ghislain, Vincent Poitout -- Gut hormone regulation and secretion via FFA1 and FFA4 / Fiona M. Gribble, Eleftheria Diakogiannaki, Frank Reimann -- FFA2 and FFA3 in metabolic regulation / Cong Tang, Stefan Offermanns -- Anti-inflammatory and insulin-sensitizing effects of free fatty acid receptors / Junki Miyamoto, Mayu Kasubuchi, Akira Nakajima, Ikuo Kimura -- Free fatty acid receptors and cancer: from nutrition to pharmacology / Mandi M. Hopkins, Kathryn E. Meier.